Size structure and length-length relationships for two shark species (Chondrichthyes: Carcharhiniformes) from an artisanal fishery in the Gulf of Tehuantepec, Southern Mexico - Celaya-Castillo, Cristina; Romero-Berny, Emilio I.; López-Vila, Jesús M.; Arias-Aréchiga, Juan P. (Revista de Biología Marina y Oceanografía, 2022)
This paper presents size structure by sex and length-length relationships for Carcharhinus falciformis and Sphyrna lewini caught by an artisanal fishery in the Gulf of Tehuantepec, Mexico. According to a local processing practice in this fishery, when sharks are landed, their jaws are removed but not their heads. The orbit-fork length was evaluated as a basis for estimating total length. A good fit (r2 > 0.9) of linear regression models for length-length relationships was calculated for both species. Overall data showed that this area is an important habitat for juvenile sharks, and standardizing measurements is proposed to better characterize the catch structure.